GEOLOGI DAERAH LANSOT DAN SEKITARNYA, KECAMATAN TARERAN, KABUPATEN MINAHASA SELATAN, SULAWESI UTARA: GEOLOGI DAERAH LANSOT DAN SEKITARNYA, KECAMATAN TARERAN, KABUPATEN MINAHASA SELATAN, SULAWESI UTARA - Mewengkang, Berliano; Momongan, Andrew; Rachmadhan, H.D. (LPPM Universitas PRISMA, 2025)
Study area is located in North Sulawesi, precisely in Lansot Village, Tareran District, South Minahasa Regency. This research aims to investigate the geological conditions of the area, including geomorphological parameters, stratigraphy, petrology, and petrography, as well as to reconstruct its geological history, which will be presented in a 1:25,000-scale geological map. The methods employed in this study include SRTM image analysis, field observations, and laboratory analysis of rock samples.Geomorphologically, the study area is divided into three landform units: the remaining hills (VD4), Dissected Volcanic Slopes (VD2), and Pyroclastic Ridge Flow (V12). Stratigraphically, the rock succession in the area, from oldest to youngest, consists of: Rumoong Lansot Tuff, Lapi Tuff, and Tumaluntung Tuff. The geological structures in the area are the result of rock and crustal deformation that has occurred over thousands of years. The geological history of the study area began when it was still part of the ancient Tondano volcano, which later collapsed due to a major explosive eruption, giving rise to younger volcanic centers that became the sources of Quaternary volcanic rocks (Qv).